The ecology of tree reproduction in an African medium altitude rain forest. (16th May 2018) - Babweteera, Fred; Plumptre, Andrew J.; Adamescu, Gabriela S.; Shoo, Luke P.; Beale, Colin M.; Reynolds, Vernon; Nyeko, Philip; Muhanguzi, Geoffrey
Abstract: The occurrence of flowering and fruiting in tropical trees will be affected by a variety of factors, linked to availability of resources and suitable climatic triggers, that may be affected by increasing global temperatures. Community‐wide flowering and fruiting of 2526 trees in 206 plots were monitored over 24 years in the Budongo Forest Reserve (BFR), Uganda. Factors that were assessed included the size of the tree, access to light, the impacts of liana load, effects of tree growth, and variation between guilds of trees. Most flowering occurs at the end of the long dry season from February to April. Trees that had access to more light flowered and fruited more frequently. Pioneer and non‐pioneer light‐demanding species tended to reproduce more frequently than shade‐bearing species. Trees that grew faster between 1993 and 2011 also fruited more frequently. When examining all factors, growth rate, tree size, and crown position were all important for fruiting, while liana load but not growth rate was important in reducing flowering. Trees in BFR show a large decline in fruiting over 24 years, particularly in non‐pioneer light demanders, shade‐bearers, and species that produce fleshy fruits eaten by primates. The decline in fruit production is of concern and is having impacts on primate diets and potential recruitment of mahogany trees. Whether climate change is responsible is unclear, but flowering of the guilds/dispersal types which show declines is correlated with months with the coolest maximum temperatures and we show temperature has been increasing in BFR since the early 1990s.